Proposed strategies to overcome venous occlusion in the implantation of a cardiac implantable electronic device: A case report and literature review - Li, Yi-Pan; Lee, Cheng-Han; Chen, Ju-Yi (Frontiers in Cardiovascular Medicine, 2022)
This case report describes a successful balloon venoplasty to overcome a total occlusion from the innominate vein to the superior vena cava in a patient undergoing cardiac resynchronization therapy. It is crucial for implanting physicians to become familiar with strategies to overcome venous occlusion in lead implantation, especially balloon venoplasty, which is an effective and safe approach.